Hybrid methods for a countable family of G-nonexpansive mappings in Hilbert spaces endowed with graphs - Suthep Suantai (2020)
© 2019 by the authors. In this paper, we introduce the iterative scheme for finding a common fixed point of a countable family of G-nonexpansive mappings by the shrinking projection method which generalizes Takahashi Takeuchi and Kubota's theorem in a Hilbert space with a directed graph. Simultaneously, we give examples and numerical results for supporting our main theorems and compare the rate of convergence of some examples under the same conditions.